The displacement and attraction effects in interurban migration: An application of the input-output scheme to the case of large cities in Korea - Cheol-Joo Cho (Kiel Institute for the World Economy (IfW), 2017)
In this paper, two migratory impact-assessment schemes are constructed within the framework of Ghoshian and Leontief input-output analysis. These schemes are designed to estimate the rural-to-urban migration-induced and the urban-to-rural migration-induced effects on interurban migration, where the former effect is termed the replacement effect, while the latter the attraction effect. The established input-output schemes are empirically applied to the 2012 data on interregional migration in Korea. The results show that an arrival of migrants to and/or a departure of residents from the 20 largest cities in Korea induce direct and indirect ripples of population flow between those cities. A combination of the displacement and the attraction effects yields a classification of cities by which the 20 largest cities are grouped into four different types.
Keywords: D57; R15; R23; R58; 330; interregional migration; displacement effect; attraction effect; input-output schemes; classification of cities; largest cities in Korea